Termination fees and contract design in public-private partnerships - Marco Buso; Cesare Dosi; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2018)
We study the effects of granting an exit option that enables the private party to early terminate a PPP project if it turns out to be loss-making. In a continuous time setting with hidden information about stochastic operating profits, we show that a revenue-maximizing government can optimally trade-off direct subsidies for capital investment against the right of opting out the PPP. In particular, the exit option, acting as a risk-sharing device, can soften agency problems and increase the value-for-money of public spending, even while taking into account the budgetary resources needed to resume the project in the event of early termination by the contractor.
Keywords: D81; D82; D86; H54; 330; Public Projects; Public-private Partnerships; Adverse Selection; Real Options; Investment Timing; Termination Fees